Gentrification and pioneer businesses - Kristian Behrens; Brahim Boualam; Julien Martin; Florian Mayneris (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2019)
We study gentrification at a micro-geographic scale using information on residents and businesses in New York from 1990 to 2010. We exploit atypical location decisions of businesses to identify the sectors that usually locate in wealthy neighborhoods but are overrepresented in poor soon-to-gentrify areas. These pioneer sectors-mostly cultural, recreational, and creative industries-help us to better predict gentrification at its early stage: including the presence of pioneers improves the accuracy of the prediction of future gentrifying spots by up to 200 meters. We show that pioneers foster gentrification through the types of workers they hire, their signal as to the future prospects of a neighborhood, and their effect on the subsequent arrival of consumption amenities.
Keywords: 330